Characterization of the flanking region of the Shiga toxin operon in Stx2a bacteriophages reveals a diversity of the NanS-p sialate O-acetylesterase gene - Pascal, Stefanía Belén (2023)
Shiga toxin-producing E. coli (STEC) are diarrheagenic strains that can cause bloody diarrhea and hemolytic-uremic syndrome. Their main virulence factor, the Shiga toxin (Stx), is encoded by phages integrated into the bacterial chromosome. Stx phages are widely diverse and carry many genes with limited or unknown function. As the toxin subtype Stx2a is associated with highly pathogenic strains, this study was mainly focused on the characterization of the stx flanking region of Stx2a phages. Of particular interest was a sialate O-acetylesterase (NanS-p), which has been described previously to be encoded downstream stx in some phage genomes and may confer a growth advantage for STEC. Complete DNA sequences of Stx2a phages and prophages were retrieved from the GenBank database, and the genomic regions from anti-terminator Q to holin S genes were bioinformatically analyzed. Predicted NanSp sequences from phages encoding other Stx subtypes were also studied. Additionally, expression of nanS-p was quantified by qPCR in strains selected from our laboratory collection. The analysis of Stx2a phage genomes showed that all carried the Q, stx2a, nanS-p and S genes, but with allele diversity and other sequence differences. In particular, sequence differences were detected in each of the three domains of NanS-p esterases encoded by Stx2a phages and other Stx phages; however, nanS-p was not identified in the Stx2e, Stx2f and Stx2g phages analyzed. The expression of nanS-p increased in most stx2a-positive strains under phage inducing conditions, as was previously shown for stx2a. As the present work showed diversity at the Q-S region among Stx phages, and particularly in the encoded NanS-p enzyme, future studies will be necessary to evaluate if NanS-p variants differ in their activity and to assess the impact of the absence of nanS-p in certain Stx phages.